2008
DOI: 10.1021/la800555x
|View full text |Cite
|
Sign up to set email alerts
|

Separation of CO2 from CH4 Using Mixed-Ligand Metal−Organic Frameworks

Abstract: The adsorption of CO2 and CH4 in a mixed-ligand metal-organic framework (MOF) Zn 2(NDC) 2(DPNI) [NDC = 2,6-naphthalenedicarboxylate, DPNI = N, N'-di-(4-pyridyl)-1,4,5,8-naphthalene tetracarboxydiimide] was investigated using volumetric adsorption measurements and grand canonical Monte Carlo (GCMC) simulations. The MOF was synthesized by two routes: first at 80 degrees C for two days with conventional heating, and second at 120 degrees C for 1 h using microwave heating. The two as-synthesized samples exhibit ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
362
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(381 citation statements)
references
References 63 publications
12
362
2
5
Order By: Relevance
“…[7] In the last decade, metal-organic frameworks (MOFs) have attracted considerable attention for gas storage, separation processes, drug delivery, and catalysis. [8][9][10][11][12] The possibilities to tailor the pore size over a wide range and to include further functionalities in the framework render MOFs particularly interesting for catalytic applications. [13] However, the number of catalytic applications of MOFs is still quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In the last decade, metal-organic frameworks (MOFs) have attracted considerable attention for gas storage, separation processes, drug delivery, and catalysis. [8][9][10][11][12] The possibilities to tailor the pore size over a wide range and to include further functionalities in the framework render MOFs particularly interesting for catalytic applications. [13] However, the number of catalytic applications of MOFs is still quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…3 Bae et al synthesized a mixed-ligand MOF, Zn 2 (NDC) 2 (DPNI) [NDC ϭ 2,6-naphthalenedicarboxylate, DPNI ϭ N,N=-di-(4-pyridyl)-1,4,5,8-naphthalene tetracarboxydiimide], and found that this material shows a selectivity of ϳ30 for CO 2 over CH 4 by using the ideal adsorbed solution theory (IAST). 6 Demessence et al synthesized an air-and water-stable MOF, H 3 [(Cu 4 Cl) 3 -(BTTri) 8 ] (H 3 BTTri ϭ1,3,5-tris(1H-1,2,3-triazol-5-yl)benzene). 13 Their results proved that the CO 2 uptakes of this material reach 142.56 mg/g at 298 K and 1 bar, while exhibiting significantly higher uptakes of CO 2 at even lower pressure after functionalized by ethylenediamine.…”
mentioning
confidence: 99%
“…The applicability of IAST to CO 2 / CH 4 separation in MOFs has indeed been validated in recent work by Snurr et al, by comparison with GCMC simulations of the adsorbed mixtures. 13 The method we propose here consists of combining the osmotic ensemble framework (eq 1) with IAST to predict the evolution of structural transitions upon adsorption of gas mixtures. Our theory is thus based exclusively on purecomponent adsorption isotherms.…”
mentioning
confidence: 99%